Tubercular Mycobacterial Spindle Cell Pseudotumour: A Case Report - Dhibar, Deba Prasad (Iran J Med Sci, 2018)
Pseudotumour is a benign inflammatory lesion. Mycobacterial spindle cell pseudotumour (MSP) is a rare pseudotumour. It is a benign proliferation of spindle-shaped histiocytes containing acid-fast mycobacterium, commonly reported in immunocompromised patients. MSP is usually associated with mycobacterium avium complex (MAC). Here, we present the case of a 38-year-old gentleman with acquired immune deficiency syndrome (AIDS) who presented with low-grade fever for 1-month duration. Clinically, he had generalised lymphadenopathy. Chest X-ray showed miliary infiltration in bilateral lung fields. Lymph nodal biopsy showed spindle-shaped histiocytes filled with acid-fast bacilli on Ziehl-Neelsen (ZN) stain, suggestive of MSP. Immunohistochemical (IHC) stains were positive for CD68, S-100 and negative for CD31, which are consistent with MSP. Polymerase chain reaction (PCR) of the biopsy tissue was positive for MTB. Highly active antiretroviral therapy (HAART) was continued and anti-tubercular therapy (ATT) was started. The fever resolved within two weeks and there was a resolution of lymph nodal swelling by 6 weeks. The diagnosis of MSP associated with mycobacterium tuberculosis (MTB) makes our case interesting. It is of utmost importance to differentiate MSP from Kaposi’s sarcoma (KS) and other pseudotumours and to know whether it is of tubercular or non-tubercular origin, as the treatment is entirely different.